Penggunaan Media Sosial Dalam Aktivitas Jual-Beli Online di Kalangan Masyarakat (Studi Kasus : Pada Pelaku Usaha Online Shop di Kota Serang) - M Dissha Najiah Al Yas'a; Susvia Delta Kusdiane; Afaf Fadhila Adzkia; Ega Jalaludin; Baandaalr Lizein (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
The rapid development of technology has facilitated access to information and influenced the pattern of people's economic activities, including in the field of buying and selling. Trade that was originally carried out conventionally has now begun to shift to digital platforms, especially social media. This study aims to examine the use of social media in online buying and selling activities by business actors in Serang City. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation of six online business actors. The results showed that online buying and selling activities through social media are generally carried out as a hobby and spare time filler, not as a main job. Businesses utilize various platforms such as WhatsApp, Facebook, Instagram, and TikTok, and pay attention to the visual quality of products to attract consumers. Interestingly, consumers' decision to buy products is not solely based on need, but is also influenced by popular trends. This phenomenon shows that social media not only serves as a marketing tool, but also influences people's consumptive behavior. Keywords: Social Media, Online Buying and Selling, Society.